The Effects of Health Promotion Literacy Program on Knowledge and Health Behaviors of National Health Recommendations among Middle School Students - Khamwichai, Kanyarat; Yurahan, Natchapat; Srisiri, Sununta; Moungsirithum, Pimpa (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2021)
This study was examined the effect of health promotion literacy program on knowledge and health behaviors of Ten National Health Recommendations among middle school students. Classroom action research was implemented among grade 8 students at middle school students selected purposively. Two comparable schools were assigned to the online Health Promotion Literacy Program for 3 weeks. The instruments employed in the study consisted of Health Promotion Literacy Program, questionnaire on knowledge and health behaviors, and user satisfaction survey. It revealed there was a significant difference in the learning achievement of health literacy and health behaviors of each school those who were participated in Health Promotion Literacy Program who performed posttest better than pretest the programme (t1=24.26, P1=0.000, t2=26.33, P2=0.000). It revealed there was an insignificant difference in the learning achievement of health literacy and health behaviors of both affiliations that it is shown that students who come from different schools totally have similar knowledge, perceptions, and behaviors (t=1.22, P=0.848). The students who participated in health promotion literacy program had satisfaction at good level (x ̅=4.39). From the study, health literacy promotion program on health behaviors according to the National Health Recommendations can positively affects student learning outcomes.